The Wind Environment Interactions Relative to Launch Vehicle Design - Johnson,Dale L. (2020)
ABSTRACT Since atmospheric winds play the most critical natural enviroment (NE) role as input into the design and development of an aerospace launch vehicle, this paper provides a more detailed description of the wind environment and its interaction with engineering design in launch and space vehicle development applications at Kennedy Space Center (KSC).